The application of AI-assisted music therapy tools in mental health interventions - Wei, Qiuyan; He, Wenting (Frontiers in Psychology, 2026)
With the rising prevalence of mental health problems across populations, the limitations of traditional interventions have become more evident. Music therapy has received growing attention as a psychological intervention, and recent advances in artificial intelligence (AI) have created new opportunities for this field. This review examines the application potential and implementation pathways of AI-assisted music therapy tools for mental health interventions. Drawing on the literature and representative cases, this review summarizes application models and reported effects of AI in music therapy. The available evidence suggests that AI-assisted music therapy tools can support personalized interventions by adapting to users’ emotional and psychological states. Reported benefits include reductions in anxiety and depressive symptoms and improvements in emotion regulation across groups such as children, adolescents, and older adults. Finally, this review outlines priorities for future translation into mental health services and emphasizes data privacy and ethical standards to ensure responsible deployment.